Analisis Jenis Child Abuse yang Mempengaruhi Tingkat Kemandirian Anak Sekolah Kelas 5-6 di SDN Karang Bayat 01 Kecamatan Sumberbaru Kabupaten Jember - Siti Zainab; Achmad Kusyairi; Iin Aini Isnawati (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
School-aged children are those within the age range of 6-12 years. The primary developmental task for school-aged children is to develop a sense of independence. Independence is the ability or attitude acquired by an individual to perform tasks on their own without the help of others. To enhance their independence, children need stimulation from their environment, such as from their parents. However, in reality, many parents resort to violence under the guise of disciplining their children by administering punishment. This study aims to analyze the corelation between types of child abuse and their impact on the level of independence of fifth and sixth grade students at SDN Karang Bayat 01, Sumberbaru, Jember. This research was a correlational analytic design with a cross-sectional approach. The study population conssisted of 39 individuals selected used purposive sampling techniques. The research instrument utilized a questionnaire. Statistical tests were conducted on the obtained data. Bivariate analysis using Chi-Square tests and logistic regression was performed to identify dominant factors. The study results indicated that physical abuse had a p-value of 0.046, verbal abuse had a p-value of 0.012, and neglect had a p-value of 0.424. This suggests that there is a corelation between physical and verbal abuse and independence, whereas neglect does not show a corelation with independence. Among the types of child abuse, verbal abuse was found to be the dominant factor affecting independence, with an Odds Ratio (OR) of 16.667. Verbal abuse by parents impacts the child’s self-confidence, which is one of the indicators of independence. It is hoped that parents will be mindful of their words and expressions towards their children to avoid hindering their independence.